KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINDAKLANJUTI PERUBAHAN KURIKULUM DI SMP NEGERI 4 PALOPO - Ramadhani, Nirja; Taqwa, Taqwa; Guntur, Muhammad (Jurnal Manajemen Pendidikan, 2025)
This study aims to determine the form of managerial competence of school principals in following up curriculum changes at SMP Negeri 4 Palopo; To find out the managerial steps of school principals in following up curriculum changes at SMP Negeri 4 Palopo. The type of research used is qualitative research. The subjects of this research were principals and teachers. The research data were obtained through interviews, documentation, and observation with data analysis using processing/organizing raw materials, sorting data based on the results of rewriting, coding data according to the characteristics of the information, analytically extracting data coherence, identifying meaningful relationships between data with one another, transposing data in the form of charts, describing meaning and rewriting about the explanation of meaning. The results of this study explain that the form of managerial competence of principals at SMP Negeri 4 Palopo in following up curriculum changes is reflected in the application of data-based planning, collaboration through learning communities, and the use of technology such as e-performance systems and ARKAS applications to support transparency and data-based evaluation. Managerial steps that include planning, organizing, directing, and supervising are carried out with reflective, collaborative, and transformational approaches to empower teachers and ensure readiness for the Merdeka Curriculum.